A Pragmatic Analysis of Politeness Maxims in Indonesian Online Customer Service Interactions - Jawas, Effa Chalisah; Yanti, Dewi; Hizbullah , Nur (JOLLT Journal of Languages and Language Teaching, 2025)
This study aims to analyze the application of Leech's politeness principles (1983) in conversations between customer service agents and customers at a property rental company, TRV (company initials), conducted via live chat. Using a qualitative approach, the research identifies and classifies the politeness maxims used in 12 selected chat interactions over a three-month period. The findings reveal that all six of Leech's politeness maxims—tact, generosity, approbation, modesty, agreement, and sympathy—are present in the data. Among them, the modesty and sympathy maxims are the most frequently used found during the searching for the sources, highlighting the importance of humility and empathy in customer service communication. The agreement maxim also plays a significant role in facilitating mutual understanding, particularly regarding scheduling and service costs. Overall, the study demonstrates that the application of politeness principles contributes to improving communication quality, fostering harmonious relationships, and enhancing the overall customer experience. This implication provides for further recommendation in online customer service replies to be standardized by the company in terms of politeness.